Between urgency and reconciliation: the great Argentina press and the enactment of the Law of “Punto Final” in 1986 - Borrelli, Marcelo (2019)
This article discusses how Argentine newspapers Clarín, La Nación and La Prensa informatively built the enactment of the Act called "Punto final" in December 1986 -during the government of Raul Alfonsín (1983-1989)-, which stipulated a deadline for filing legal complaints against members of the Argentine armed forces who had committed crimes during the clandestine repression ordered by the military dictatorship between 1976 and 1983. In a context where the military pressured the government not to be judged, the publications studied construct a scenario of urgency and need for reconciliation to resolve the conflict.